Role of astrocytes in sleep deprivation: accomplices, resisters, or bystanders? - Que, Mengxin; Li, Yujuan; Wang, Xuan; Zhan, Gaofeng; Luo, Xiaoxiao; Zhou, Zhiqiang (Frontiers in Cellular Neuroscience, 2023)
Sleep plays an essential role in all animals endowed with a nervous system that have been carefully studied, and sleep deprivation can lead to the development of various physiological and neurobehavioral problems. Astrocytes are the most abundant cells in the brain and are involved in various important functions, including neurotransmitter and ion homeostasis, synaptic and neuronal modulation, and blood–brain barrier maintenance; they are also associated with many degenerative brain diseases, pain, and mood disorders. Moreover, astrocytes are increasingly being recognized as vital contributors to the regulation of sleep-wake cycles, both locally and in dedicated neural circuits. In this review, we begin by describing the role of astrocytes in regulating sleep and circadian rhythms, focusing on: (i) neuronal activity; (ii) metabolism; (iii) the glymphatic system; and (iv) neuroinflammation and (v) astrocyte–microglia cross-talk. We then discuss the role of astrocytes in sleep deprivation comorbidities and related brain disorders. Finally, we discuss potential interventions targeting astrocytes to prevent or treat sleep-associated brain disorders. Pursuing these questions will pave the way for an understanding of the cellular and neural mechanisms underlying sleep deprivation-comorbid brain disorders.